Stability of a TDMA Network Subject to Finite Blocklength Constraints - Kourtellaris, Christos K.; Psomas, Constantinos; Krikidis, Ioannis (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
Recent advances in information theory have provided a novel framework regarding finite blocklength analysis, which can be employed to address the current and future demands of communication networks. In this paper, we investigate the performance of the Time-Division Multiple-Access (TDMA) scheme with bursty traffic, subject to finite blocklength constraints. In contrast to previously reported work, where the analysis of such communication networks was performed under the infinite blocklength assumption, we develop a comprehensive framework that takes finite blocklength constraints into account. In particular, we employ the recent results in finite blocklength analysis, to prove necessary stability conditions for the overall system at the finite blocklength regime, and to identify the optimal trade-off between data length and channel blocklength. The later one is evaluated both numerically and via the proposed linear and quadratic approximations that result to closed form expressions.